2015
DOI: 10.1097/mbc.0000000000000296
|View full text |Cite
|
Sign up to set email alerts
|

Effect of serum monoclonal protein concentration on haemostasis in patients with multiple myeloma

Abstract: Abnormalities in haemostasis are often detected in patients with multiple myeloma and the fundamental factors that lead to these abnormities are worthy of exploration. The objective of this study was to investigate bleeding diathesis and coagulopathy in different multiple myeloma types or stages and assess how paraprotein concentration contributes to differences in these conditions. Haemostasis screening tests and serum monoclonal protein (M protein) concentration were retrospectively analysed in 101 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 21 publications
3
21
0
Order By: Relevance
“…Light chain paraprotein might have a stronger nonspecific binding effect to fibrinogen and can affect TT more likely than other immunoglobulin types. In most cases TT prolongation was accompanied by a prolonged PT, suggesting that TT is more sensitive to the presence of monoclonal protein than PT [22]. This hypothesis is in line with our observations.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Light chain paraprotein might have a stronger nonspecific binding effect to fibrinogen and can affect TT more likely than other immunoglobulin types. In most cases TT prolongation was accompanied by a prolonged PT, suggesting that TT is more sensitive to the presence of monoclonal protein than PT [22]. This hypothesis is in line with our observations.…”
Section: Discussionsupporting
confidence: 91%
“…Post et al [19] and Xin-yao [20] showed that the PT, but not APTT, was positively correlated with serum paraprotein level, regardless of the reagents and instrumentation used to assess clotting time. Huang et al [21] and Pandey et al [22] confirmed this finding and, more importantly, showed a strong correlation between TT prolongation and total light chain (not M protein) concentration. Prolonged TT most likely results from acquired dysfibrinogenemia, secondary to multiple myeloma.…”
Section: Discussionmentioning
confidence: 74%
“…The mean free light chain concentration in k light chain myeloma was 1727mg/L with a mean PT value of 20.5 s, mean aPTT value of 37.4s and a p-value of 0.026 which was statistically significant. So, mean immunoglobulin concentration in our study was significantly higher in patients with prolonged PT and aPTT compared to that of patients with normal PT and aPTT values and was positively correlated with the studies conducted by Pandey et al, Huang H et al and Teng et al 12,13,14…”
Section: Discussionsupporting
confidence: 87%
“…The critical appraisal of the above research areas will establish the necessity of combining disease-specific clinical risk factors with coagulation biomarkers to allow more effective risk stratification that will eventually lead to the reduction of this significant complication. Results from ongoing clinical trials on the role of DOACs are much anticipated.Cancers 2020, 12, 191 2 of 17 managing the complications and adverse effects of these therapeutic agents, including the management of VTE [10].Thrombogenicity in MM is multifactorial, and risk factors are traditionally distinguished in three groups [11,12]: patient-related clinical risk factors, disease-related risk factors, and treatment-related risk factors. It has become evident from clinical trial data during the last decade that immunomodulatory agents among anti-myeloma treatments stand out as having a considerable prothrombotic effect.…”
mentioning
confidence: 99%
“…Thrombogenicity in MM is multifactorial, and risk factors are traditionally distinguished in three groups [11,12]: patient-related clinical risk factors, disease-related risk factors, and treatment-related risk factors. It has become evident from clinical trial data during the last decade that immunomodulatory agents among anti-myeloma treatments stand out as having a considerable prothrombotic effect.…”
mentioning
confidence: 99%